Animal management and welfare in natural disasters - Sawyer, James, 1875-; Huertas, Gerardo; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
The devastating impacts of natural disastersnot only directly affect humans and infrastructure, but also animals, which may be crucial to the livelihoods of many people.This bookconsiders the needs of animals in the aftermath of disasters and explains the importance of looking to their welfare in extreme events. The authors explore how animals are affected by specific disaster types, what their emergency and subsequent welfare needs are and the appropriate interventions.They describe the key benefits of management of animals to populations and discuss preventative measures that can be taken to reduce risk and build resilience. Theyalso include a summaryof recent debates and public policy advances on animals in disasters. The book covers livestock, companion and wild animals, with case studies to show how the concepts can be put into practice. It provides a standalone text for students of disaster studies and management as well as professionals and NGOs who require an entry-level introduction to the subject.Why Help Animals in Disaster?.
chapter 1 Why help animals in disasters? -- chapter 2 Key principles and mechanisms of disaster management -- chapter 3 The impact of disasters on animal welfare -- chapter 4 The immediate rescue of animals -- chapter 5 Immediate relief for animals -- chapter 6 Supporting the recovery of animals -- chapter 7 Preparing people and animals for disasters -- chapter 8 Reducing risk for animals vulnerable to disasters -- chapter 9 The role of animal professionals in disasters -- chapter 10 The future for animal welfare in disasters.
Keywords: Animal Welfare; Animals; Disaster Planning; Disasters; Emergency management; TECHNOLOGY & ENGINEERING / Agriculture / Animal Husbandry; Animal Welfare; Animals; Disaster Planning; Disasters